Bahasa Inggris Bahasa Inggris - Abdul Malik Sayuti; Sharnuke Asrilsyak; Wahyu Rafdinal (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
Employees are the main capital for company development. Company needs the best employee’s performance to advance and achieve their goals. To support this, many supporting factors such as leadership style, quality of work life and organizational citizenship behavior are needed to stimulate employees giving their optimum contributions by finalize their work effectively and efficiently. This study analyzes the effect of spiritual leadership style on the quality of work life, organizational citizenship behavior on employee’s performance. The data in this study were obtained by distributing questionnaires to 100 employees of the Islamic Hospital in West Sumatra as research respondents. Path analysis is used as data analysis method in this study. The results of the study prove that: 1) the spiritual leadership style significantly influences the quality of work life, 2) the spiritual leadership style has a significant effect on organizational citizenship behavior, 3) the quality of work life has a significant effect on organizational citizenship behavior, 4) the spiritual leadership style significantly influences employee’s performance, 5) quality of work life has a significant effect on employee’s performance, 6) organizational citizenship behavior significantly influences employee’s performance. This study implicates that leaders or managers can enhance the role of spiritual leadership to improve the employee’s quality of work life and organizational citizenship behavior in institutions they lead. So that, the spiritual leadership will directly or maybe indirectly encourage employee performance improvement.